Injury trends and prevention in youth resistance training - Faigenbaum, Avery D. (National Strength and Conditioning Association journal.)
Resistance training has become a popular method of conditioning for children and adolescents in schools, recreation centers, and sports training facilities. However, the growing popularity of youth resistance training and the complex nature of some training programs raise new questions and concerns about the safety of this type of training for youth. In this article, the incidence, severity, and etiology of youth resistance training injuries are reviewed, risk factors for resistance training-re-lated injuries are identified, and injury prevention strategies for youth who perform resistance exercise are discussed.